Understanding the transcriptomic response of Lactiplantibacillus pentosus LPG1 during Spanish-style green table olive fermentations - López-García, Elio; Benítez-Cabello, Antonio; Tronchoni, Jordi; Arroyo-López, Francisco Noé (Frontiers in Microbiology, 2023)
Lactiplantibacillus pentosus (Lbp. pentosus) is a species of lactic acid bacteria with a great relevance during the table olive fermentation process, with ability to form non-pathogenic biofilms on olive epidermis. The objective of this work is to deepen into the genetic mechanisms of adaptation of Lpb. pentosus LPG1 during Spanish-style green table olive fermentations, as well as to obtain a better understanding of the mechanisms of adherence of this species to the fruit surface. For this purpose, we have carried out a transcriptomic analysis of the differential gene expression of this bacterium during 60 days of fermentation in both brine and biofilms ecosystems. In brines, it was noticed that a total of 235 genes from Lpb. pentosus LPG1 were differentially expressed during course of fermentation and grouped into 9 clusters according to time-course analysis. Transport and metabolism of carbohydrates and amino acids, energy production, lactic acid and exopolysaccharide synthesis genes increased their expression in the planktonic cells during course of fermentation. On the other hand, expression of genes associated to stress response, bacteriocin synthesis and membrane protein decreased. A total of 127 genes showed significant differential expression between Lpb. pentosus LPG1 planktonic (brine) and sessile (biofilms) cells at the end of fermentation process (60 days). Among the 64 upregulated genes in biofilms, we found genes involved in adhesion (strA), exopolysaccharide production (ywqD, ywqE, and wbnH), cell shape and elongation (MreB), and well as prophage excision. Deeping into the genetic bases of beneficial biofilm formation by Lpb. pentosus strains with probiotic potential will help to turn this fermented vegetable into a carrier of beneficial microorganisms to the final consumers.